Towards characterizing the adaptive capacity of farmer-managed irrigation systems: learnings from Nepal - and Thapa, Bhuwan; Scott, Christopher; Wester, Philippus; Varady, Robert (Environmental change assessments, 2016)
Small-scale irrigation systems managed by farmers are facing multiple challenges including competing water demand, climatic variability and change, and socioeconomic transformation. Though the relevant institutions for irrigation management have developed coping and adaptation mechanisms, the intensity and frequency of the changes have weakened their institutional adaptive capacity. Using case examples mostly from Nepal, this paper studies the interconnections between seven key dimensions of adaptive capacity: the five capitals (human, financial, natural, social, and physical), governance, and learning. Long-term adaptation requires harnessing the synergies and tradeoffs between generic adaptive capacity that fosters broader development goals and specific adaptive capacity that strengthens climate-risk management. Measuring and addressing the interrelations among the seven adaptive-capacity dimensions aids in strengthening the long term sustainability of farmer-managed irrigation systems.